8.29. Sprawdź, czy wielomiany w(x) = (3x – 1)(4 – 2x) * (x + 1) b) w(x) = (3 – 5x) ^ 2 * (x ^ 2 – 1) – 25x ^ 4 cw w(x) = (- 2x + 1) ^ 3; w(x) = 3x ^ 5 – (2x ^ 2 + 1)(x ^ 3 – 1) d) W w(x) i P(x) są równe, jeśli: P(x) = – 6x ^ 3 + 8x ^ 2 + 10x – 4; P(x) = – 30x ^ 3 – 16x ^ 2 + 30x – 9; P(x) = – 8x ^ 3 + 12x ^ 2 – 12x + 1; P(x)=x^ 5 -x^ 3 +2x^ 2 +1.

8.29. Sprawdź, czy wielomiany w(x) = (3x – 1)(4 – 2x) * (x + 1) b) w(x) = (3 – 5x) ^ 2 * (x ^ 2 – 1) – 25x ^ 4 cw w(x) = (- 2x + 1) ^ 3; w(x) = 3x ^ 5 – (2x ^ 2 + 1)(x ^ 3 – 1) d) W w(x) i P(x) są równe, jeśli: P(x) = – 6x ^ 3 + 8x ^ 2 + 10x – 4; P(x) = – 30x ^ 3 – 16x ^ 2 + 30x – 9; P(x) = – 8x ^ 3 + 12x ^ 2 – 12x + 1; P(x)=x^ 5 -x^ 3 +2x^ 2 +1.